Effect of Certain Drugs on Treatment of Canine Pyometra with Special Reference to Kidney and Heart Function - Kumar, Mohit; Kumar, Anuj; Sachan, Vikas; Saxena , Atul (The Indian Journal of Animal Reproduction, 2024)
Pyometra, literally meaning pus in the uterus, is a disease of the uterus in intact, sexually mature bitches. The present study focuses on evaluation of different therapeutic protocol for treatment of canine pyometra based on haemato-biochemical parameters with special emphasis on kidney and heart function. A total of 18 female dogs were clinically diagnosed for pyometra at the department of Veterinary Gynaecology and Obstetrics, DUVASU, Mathura (U.P). These animals were divided into three Groups (Group II, III and IV) having 6 female dogs in each group and 6 healthy females were kept in Group I as control. All pyometra animals were treated with amoxicillin-clavulanic acid @ 25 mg/kg b.wt./day via intravenous route and intrauterine route for 9 days along with fluid therapy. Before giving hormonal treatment, all pyometra animals were treated with atropine @ 0.025 mg/kg b.wt and ondansetron @ 0.5 mg/kg b.wt. via intramuscular route. Cloprostenol @ 5 μg/kg b.wt on day 1, 3, 5, 7, 9 (subcutaneous route in Group II & IV and intravaginal route in Group III), tab mifepristone @ 2.5 mg/kg b.wt on day 2, 4, 6, 8 orally and tab cabergoline @ 5μg/kg b.wt on day 1, 2, 3, 4, 5, 6, 7, 8 orally provided in all pyometra groups. Nephroprotective drug having Taurine and N-Acetyl cysteine was given in Group IV for 14 days. Mean values of haemato-biochemical parameters altered significantly in canine pyometra. The therapeutic protocol in Group II, III and IV showed success rate of 83.33 and 66.63, 100%, respectively.